A performance-oriented account of money awards for breach of contract - Winterton, D (2011)
It is generally accepted that the award of contract damages in English law is governed by the expectation principle. This principle provides that following an actual or anticipated breach of contract the innocent party is entitled to be put into the position that he or she would have occupied had the contract been performed. There is significant ambiguity over what ‘position’ means in this context. The conventional understanding of the expectation principle is that it stipulates the appropriate measure of loss for an award of compensation. This thesis challenges this understanding and proposes a new performance-oriented account of awards given in accordance with the expectation principle. The thesis is in two parts. Part I outlines and challenges the orthodox understanding of awards given in accordance with the expectation principle. Chapter One outlines the orthodox account, and explains the traditional interpretation of loss in this context. Chapter Two mounts a doctrinal challenge to the orthodox account, demonstrating the existence of many awards for breach of contract that do not reflect the actual loss suffered by the innocent party. Chapter Three highlights the conceptual difficulty of the orthodox account and outlines the problems with conventional terminology, proposing stable definitions for important legal concepts. Part II advances an alternative account of contract damages that draws a distinction between two different kinds of money awards. The first is an award substituting for performance. The second is an award compensating for loss. Chapter Four outlines the account’s foundations by defending the existence of the right to performance and the existence of the proposed distinction. Chapter Five explains the quantification and restriction of money awards substituting for performance. Chapter Six explains the nature of money awards compensating for loss. Finally, Chapter Seven defends English law’s preference for awarding monetary substitutes for performance rather than ordering specific performance.